2016
DOI: 10.1186/s12886-016-0300-7
|View full text |Cite
|
Sign up to set email alerts
|

A cyclic vertical deviation with dysthyroid ophthalmopathy: a case report

Abstract: BackgroundCyclic strabismus is a very rare condition of ocular motility characterized by alternating strabismus and orthotropia. We report a patient with a 48-h cycle of vertical deviation associated with dysthyroid ophthalmopathy that spontaneously resolved.Case presentationA 40-year-old woman experienced sudden onset vertical double vision. She had already been diagnosed with hyperthyroidism. Asymmetric enlargement of the inferior and medial rectus muscles was demonstrated in her left eye on computed tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Cyclic strabismus is not known to have a mechanism, although biological clocks and diurnal and circadian rhythms may play a role [ 1 , 2 , 11 ]. For cyclic pattern, following theories have been proposed in the literature – aberration of the central nervous system disease [ 2 ], peripheral disease such as traumatic aphakia[3], optic atrophy [ 4 ], strabismus surgery [ 5 , 6 ], high AC/A ratio [ 7 ] and dysthyroid ophthalmopathy [ 8 ]. Children with cyclic strabismus usually begin experiencing it around 3 to 4 years of age without any triggering events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic strabismus is not known to have a mechanism, although biological clocks and diurnal and circadian rhythms may play a role [ 1 , 2 , 11 ]. For cyclic pattern, following theories have been proposed in the literature – aberration of the central nervous system disease [ 2 ], peripheral disease such as traumatic aphakia[3], optic atrophy [ 4 ], strabismus surgery [ 5 , 6 ], high AC/A ratio [ 7 ] and dysthyroid ophthalmopathy [ 8 ]. Children with cyclic strabismus usually begin experiencing it around 3 to 4 years of age without any triggering events.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of cyclic strabismus cases occur in children [ 1 ] and are idiopathic. It has been reported that adult-onset cyclic strabismus can be associated with central nervous system [ 2 ] and peripheral diseases, such as traumatic aphakia [ 3 ], optic atrophy [ 4 ], strabismus surgery [ 5 , 6 ], high AC/A ratio [ 7 ] and dysthyroid ophthalmopathy [ 8 ], but no case of cyclic strabismus with axial high myopia has been reported. In spite of numerous attempts to explain the pathophysiology of this condition, the exact mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%